Evaluation of safety and effectiveness of remdesivir in treating COVID-19 patients after emergency use authorization study - Burhan, Erlina; Syahruddin, Elisna; Isbaniah, Fathiyah; Desianti, Ginanjar Arum; Fachrucha, Fanny; Sari, Cut Yulia Indah; Ismail, Efriadi; Astuti, Puji; Maruli, Muhammad Farhan; Mubarak, Farhan; Rengganis, Anggit Tresna; Bilqis, Hazia Hanifa; et al. (Frontiers in Pharmacology, 2023)
Background: This study aimed to determine the real-world safety and effectiveness of remdesivir in hospitalized adult COVID-19 patients with moderate-to-critical disease in Indonesia. Methods: A multicenter, retrospective cohort study was conducted at four COVID-19 referral hospitals in Jakarta. A total of 587 patients were included, of whom 243 received remdesivir within 72 h of admission. The safety endpoints were the proportions of patients with any adverse event (AE), any grade 3 AE, and AE of each system organ class. The effectiveness endpoints were ICU admission >24 h from baseline, live discharge and mortality at day 14, live discharge and mortality at day 28, and virologic conversion. Patients who received remdesivir within 72 h of admission were considered the treatment group, and those who did not were the control group. Multivariate adjustments were performed using a modified Poisson regression. Results: The study found no significant differences in safety endpoints between the two groups. However, the effectiveness endpoints showed that remdesivir was associated with a decreased risk of ICU admission >24 h from baseline (RR 0.71, 95% CI 0.52–0.96), an increased probability of live discharge at day 14 (RR 1.37, 95% CI 1.08–1.74), and an increased probability of live discharge at day 28 (RR 1.28, 95% CI 1.05–1.57). The rate of virologic conversion was not significantly different between the two groups. Conclusion: The study concludes that remdesivir is safe and effective in the treatment of moderate-to-critical COVID-19 in a real-world setting in Indonesia.